2017
DOI: 10.3389/fphar.2017.00593
|View full text |Cite
|
Sign up to set email alerts
|

Colocynth Extracts Prevent Epithelial to Mesenchymal Transition and Stemness of Breast Cancer Cells

Abstract: Modern treatment strategies provide better overall survival in cancer patients, primarily by controlling tumor growth. However, off-target and systemic toxicity, tumor recurrence, and resistance to therapy are still inadvertent hurdles in current treatment regimens. Similarly, metastasis is another deadly threat to patients suffering from cancer. This has created an urgent demand to come up with new drugs having anti-metastatic potential and minimum side effects. Thus, this study was aimed at exploring the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…These findings were in agreement with the earlier data which showed an important antiproliferative effect on human breast cancer cells induced by cucurbitacin, isolated from the leaves of C. colocynthis [22]. The cytotoxic effects of the fruit pulp of C. colocynthis against cancer breast cell lines MCF-7 were studied [23]. Some chemical compounds revealed in the current extract such as ethylbenzene and tetrachloroethylene could determine the cytotoxic effect of C. colocynthis on HT-29 and MDA-MB-231 cell lines as to whether their effects are due to a single molecule or due to a potential synergy between them, and therefore further studies that may lead to determining the responsible compounds for the current activities are still appreciated.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were in agreement with the earlier data which showed an important antiproliferative effect on human breast cancer cells induced by cucurbitacin, isolated from the leaves of C. colocynthis [22]. The cytotoxic effects of the fruit pulp of C. colocynthis against cancer breast cell lines MCF-7 were studied [23]. Some chemical compounds revealed in the current extract such as ethylbenzene and tetrachloroethylene could determine the cytotoxic effect of C. colocynthis on HT-29 and MDA-MB-231 cell lines as to whether their effects are due to a single molecule or due to a potential synergy between them, and therefore further studies that may lead to determining the responsible compounds for the current activities are still appreciated.…”
Section: Discussionsupporting
confidence: 92%
“…The major component with the highest percentage peak area was oxalic acid, cyclobutyl octadecyl ester (24.985%) at retention time 53.478 min, followed by 4-Tridecanol and nitric acid, nonyl ester with percentage peak area of 6.359% and 5.616%, respectively. Biological activity has been performed on the compound oxalic acid, cyclobutyl octadecyl ester (Chowdury et al 2017), but in the report published by Chandrakasan and Neelamegam (2011), there is no activity performed on the hydroxyl compound i.e. methyl 2-hydroxydodecanoate and the rest of the compounds.…”
Section: Chemical Composition Of Hexane Stem Extractmentioning
confidence: 99%
“…Our findings are consistent with previous reports for some plant extracts and other existing brain tumour therapies known to inhibit colony formation in glioblastoma cells. [42][43][44][45] Altogether, these results demonstrated that both extracts of S. frutescens and C. edulis impeded colony formation as well as survival in the U251 glioblastoma and this activity was better demonstrated in cells treated with S. frutescens.…”
Section: S Frutescens and C Edulis Inhibit Colony Formation And Surmentioning
confidence: 60%